2020
DOI: 10.7771/2327-2937.1131
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Nutrition Information in Recreational Ultra-marathon Runners: A Mixed Methods Analysis

Abstract: Ultra-marathon events (i.e., .42.2-km) continue to grow in popularity; however, little is known regarding the sources of nutrition information which inform their beliefs and habits. The objective of this study was to characterize the acquisition of sport-specific nutrition information among ultra-endurance athletes using a mixed methods design. Qualitative data were collected through focus groups and analyzed using thematic analysis. Three primary higher order themes were identified: Optimal Diet for Ultra-End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…It is difficult to interpret the reported protein intake in the present study as there were a range of sporting types, intensities and abilities, although with a median intake of 1.18 grams of protein consumed per kilogram per day, it is likely that the majority of respondents consumed sufficient protein for moderate activity. The values were consistent with other studies including other athletes following vegan diets with 1.11 g/day/kg bodyweight in healthy physically active women (Boutros et al, 2020 ), 1.61 g/day of bodyweight in ultra‐runners (Mahoney et al, 2016 ; vegan and LOV combined) and 1.25 g/kg bodyweight in recreational runners (Nebl et al, 2019c ) and athletes following LOV diets with 1.34 g/kg (Nebl, Schuchardt, Wasserfurth, et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…It is difficult to interpret the reported protein intake in the present study as there were a range of sporting types, intensities and abilities, although with a median intake of 1.18 grams of protein consumed per kilogram per day, it is likely that the majority of respondents consumed sufficient protein for moderate activity. The values were consistent with other studies including other athletes following vegan diets with 1.11 g/day/kg bodyweight in healthy physically active women (Boutros et al, 2020 ), 1.61 g/day of bodyweight in ultra‐runners (Mahoney et al, 2016 ; vegan and LOV combined) and 1.25 g/kg bodyweight in recreational runners (Nebl et al, 2019c ) and athletes following LOV diets with 1.34 g/kg (Nebl, Schuchardt, Wasserfurth, et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…In line with the present study in which a considerable portion of runners were vegans and vegetarians, data indicate that the popularity of vegan and vegetarian diets in endurance runners is higher than general populations [23,66,73]. Research shows that 10% of distance runners follow a vegan/vegetarian diet, with a higher prevalence in runners competing over longer distances such as ultramarathon [25,53].…”
Section: Discussionsupporting
confidence: 88%
“…Another study showed that distance runners had a lower consumption of carbohydrates compared to other endurance athletes [65]. Differentiated findings from an investigation on ultra-marathoners indicate that there is a wide variation in their dietary intake, but it appears that they generally follow low-carbohydrate (high-protein and high-fat) diets compared to the dietary recommendations for endurance athletes [66]. While it has been well-established that training/racing behaviors of endurance runners are associated with their carbohydrate intake [23,61], dietary recommendations emphasize that endurance runners should generally consume higher amounts of carbohydrates compared to general populations [67,68].…”
Section: Discussionmentioning
confidence: 97%
“…(G*Power software, version 3.1.9.7, Franz Faul, Christian‐Albrechts‐Universität Kiel, Kiel, Germany). The sample size in this study is similar to other hypothesis‐generating studies (e.g., n = 33–47) evaluating the relationship between habitual dietary intake with gastrointestinal symptoms in ultra‐marathoners 27,28 …”
Section: Methodsmentioning
confidence: 69%
“…The sample size in this study is similar to other hypothesis-generating studies (e.g., n = 33-47) evaluating the relationship between habitual dietary intake with gastrointestinal symptoms in ultra-marathoners. 27,28…”
Section: Introductionmentioning
confidence: 99%